SUFFIXAL DERIVATION IN ADJECTIVAL UNITS OF LINGUISTIC TERMINOLOGY: STRUCTURAL, SEMANTIC AND TYPOLOGICAL EXPANSION IN ENGLISH AND UZBEK - Ahmedov Utkir Ilhomovich (International Journal of Literature and Language Studies, 2026)
This study provides an expanded structural, semantic, and typological analysis of suffixal derivation in adjectival units of linguistic terminology. The research examines how derivational suffixes (-ic, -ical, -al, -ive, -ous, -ary) function as systematic tools for encoding scientific meaning in English linguistic terminology and how similar semantic functions are realized in Uzbek through affixation and lexical borrowing. The study further explores the cognitive and systemic role of adjectival terminology in scientific discourse formation. Using qualitative descriptive, comparative, and typological methods, the paper demonstrates that suffixation is not merely a morphological process but a fundamental epistemological mechanism shaping scientific categorization. The findings highlight that English exhibits high morphological productivity in adjectival derivation, while Uzbek relies on a hybrid model of affixation and loan adaptation, resulting in structurally different but functionally equivalent terminological systems.